The possibility of effective eradication of the microorganism root canal endodontic treatment by medication (Эндодонтия Today)
Endodontic preparation of permanent teeth with incomplete root formation is a time consuming process, which is determined by a number of anatomical features characteristic of this period of development. In this connection, the purpose of the study was to evaluate the performance impact of the most commonly used antiseptics against microbiota of root canals in permanent teeth with incomplete root formation in chronic apical periodontitis in children. Was a comparative characteristic of the efficacy of endodontic antiseptics, the most commonly used at the Junior dental examination used to reorganize the system of root canals in permanent teeth with incomplete root formation, «Miramistin», 2% chlorhexidine bigluconate, «Endotin» («Septodont») and «Belodez» («VladMiVa»). The positive changes in the species composition of the picture after the drug treatment of root canals.